Time-and-Wavelength Resolved Pump Probe Spectroscopy & Calibration Measurement Using Semiconductors - M, P. Munkhbaatar; D, Ulam-Orgikh; K. Myung-Whun (Scientific transaction of the National University of Mongolia. Physics, 2022)
Pump-probe experimental setup using 10 fs ultra-short laser pulse was successfully developed. Using this setup, the excitation of coherent phonons in Te and GaAs were measured for calibration and accuracy test of the developed setup. Coherent Raman-active phonons are observed by PP experiments. 10 fs pulse was not necessary to generate coherent optical phonon. Strongly chirped pulse with roughly » 20 fs duration can generate it. Frequencies of these modes was in good agreement to values reported. It was demonstrated how spectrum of laser near of band-gap could signi cantly aect the pump-probe signal. In near of band-gap, the PP response of GaAs is dependent on the spectrum of the laser, but coherent optic phonon oscillation isn’t dependent on it. Time-and-frequency resolved pump-probe optical spectroscopy is used to investigate the eect of spectral dependence of pump-probe of GaAs. The measured modi cations of the optical properties of GaAs are consistent with the creation of a non-thermal state, metastable on the ps timescale, after the pump-induced impulsive modi cation of the electron interactions.